Hubungan Antara Burnout dengan Motivasi Kerja pada Pegawai Negeri Sipil di Dinas Pekerjaan Umum, Penataan Ruang, Perumahan dan Kawasan Permukiman Provinsi Bali - Junior Wedha; Sagung Putri Permana Lestari Murdhana Putere; Putu Asih Primatanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Workplace burnout manifests as a psychological syndrome stemming from a protracted reaction to chronic interpersonal stressors. Burnout can lead to long-term fatigue and inability to work. The burnout phenomenon affects occupations of all professions, but a large number of studies show that people with jobs that involve helping others or social workers are particularly vulnerable to burnout. Work motivation is linked to individual behavior in suppressing stress in work situations. Work motivation functions as a form of encouragement that directs a person's behavior in a challenging problem. The present investigation aimed to ascertain the correlation between burnout and work motivation in Civil Servants stationed at the Office of Public Works, Spatial Planning, Housing, and Residential Areas (DPUPRPKP) of Bali Province. This research is an analytic descriptive research with cross sectional design. The subjects in this study were 150 civil servants at the DPUPRPKP of Bali Province. The sampling technique employed was stratified random sampling. Data manipulation shall be carried out using Microsoft Excel, encompassing both univariate and bivariate analyses. The instruments utilized comprise the Maslach Burnout Inventory-General Survey (MBI-GS) questionnaire to gauge the extent of burnout, alongside the Abraham Maslow Model questionnaire to assess work motivation levels. The findings from this inquiry unveil a significant association between burnout and work motivation (p=0.000), with the correlation coefficient measuring at -0.959. This robust correlation indicates an opposing direction, wherein heightened burnout levels among civil servant correspond to diminished work motivation.